Religious Character Education Values in the Novel "Sabtu Bersama Bapak" by Adhitya Mulya and its Potential as Teaching Material for Short Story Texts - Windanty, Tyara Hastu Sekar; Sufanti, Main (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This study aims to explore the educational values and potential of religious characters in the novel "Sabtu Bersama Bapak" by Adhitya Mulya as a literature teaching material in schools. The method employed in this research is qualitative descriptive, with the subject and object of the study consisting of words or phrases found within the novel "Sabtu Bersama Bapak" by Adhitya Mulya. The primary source of data for this research is the novel itself, "Sabtu Bersama Bapak." Data collection techniques utilized in this study include literature review, observation, and note-taking. The findings of this study have revealed four out of five elements of a religious character or "Beriman," "Bertakwa Kepada Tuhan Yang Maha Esa," and "Berakhlak Mulia" as outlined in the "Profil Pelajar Pancasila" (Pancasila Student Profile). These elements include (a) religious ethics such as praying to God, expressing gratitude to the Almighty, performing religious rituals, and surrendering to God's will, (b) personal ethics encompassing sincerity, self-respect, self-care, responsibility, patience, and courtesy, (c) social ethics involving assisting those in need, respecting others with polite speech, communicating respectfully with others, advising others, and providing solutions, and (d) environmental ethics entailing a love for nature and appreciation of its beauty. Meanwhile, the potential of "Sabtu Bersama Bapak" as teaching material in this study is demonstrated through the reinforcement of students' character education via the religious character elements present in the novel.